ANALISIS PERENCANAAN PENGANGGARAN APBD PEMERINTAH - Muhammad Imam Gazali; Ikbal Ikbal; Victor Pattiasina; Ika Agustina; Eljawati Eljawati (POLITEKNIK LP3I JAKARTA, 2025)
The purpose of this study is to determine and analyze the government's APBD budget planning. This research approach collects data through literature studies, which involve reading literature from various sources including books, reports, articles, and journals using qualitative and deductive approaches. The findings in this study are that there are several stages in APBD budget planning, including the preparation of planning documents consisting of RPJPD, RPJMD, and RKPD, preparation of KUA and PPAS, preparation of RKA-SKPD, budget implementation, and administration and accountability. The effectiveness of APBD budget planning is highly dependent on the quality of planning documents, synchronization between documents (RPJPD, RPJMD, RKPD, and KUA-PPAS), internal control and supervision systems, and the commitment of regional heads to good governance. This is the main key to realizing good regional financial governance and sustainable regional development.